Primary cilia and actin regulatory pathways in renal ciliopathies - Kalot, Rita; Sentell, Zachary; Kitzler, Thomas M.; Torban, Elena (Frontiers in Nephrology, 2024)
Ciliopathies are a group of rare genetic disorders caused by defects to the structure or function of the primary cilium. They often affect multiple organs, leading to brain malformations, congenital heart defects, and anomalies of the retina or skeletal system. Kidney abnormalities are among the most frequent ciliopathic phenotypes manifesting as smaller, dysplastic, and cystic kidneys that are often accompanied by renal fibrosis. Many renal ciliopathies cause chronic kidney disease and often progress to end-stage renal disease, necessitating replacing therapies. There are more than 35 known ciliopathies; each is a rare hereditary condition, yet collectively they account for a significant proportion of chronic kidney disease worldwide. The primary cilium is a tiny microtubule-based organelle at the apex of almost all vertebrate cells. It serves as a "cellular antenna" surveying environment outside the cell and transducing this information inside the cell to trigger multiple signalling responses crucial for tissue morphogenesis and homeostasis. Hundreds of proteins and unique cellular mechanisms are involved in cilia formation. Recent evidence suggests that actin remodeling and regulation at the base of the primary cilium strongly impacts ciliogenesis. In this review, we provide an overview of the structure and function of the primary cilium, focusing on the role of actin cytoskeleton and its regulators in ciliogenesis. We then describe the key clinical, genetic, and molecular aspects of renal ciliopathies. We highlight what is known about actin regulation in the pathogenesis of these diseases with the aim to consider these recent molecular findings as potential therapeutic targets for renal